2018
DOI: 10.5812/semj.63700
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in Distribution of Health Care Resources in Iran: Human Resources, Health Centers and Hospital Beds

Abstract: Background: One of the most important goals of health systems is equality in access to health services and one of the important dimensions of health equality in relation to resources distribution in this sector. Objectives: This study was done to examine the equality in resource distribution between provinces of Iran in 2014. Methods: In the present retrospective study, the population included the public health sector human resources, hospital beds, and health centers in Iran. The data were collected from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…25 In their study about the inequality in the distribution of healthcare resources in Iran, Lofty et al found that the highest ratio of manpower number per 1000 population was in Ilam province. 29 It should be mentioned that this study does not consider the misdistribution of health workers within Ilam province. In the study by Sefiddashti regarding inequality in the distribution of human resources in Tehran province, they found that the highest value of the Gini coefficient (GC) was related to nurses (GC=0.291) in 2007.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…25 In their study about the inequality in the distribution of healthcare resources in Iran, Lofty et al found that the highest ratio of manpower number per 1000 population was in Ilam province. 29 It should be mentioned that this study does not consider the misdistribution of health workers within Ilam province. In the study by Sefiddashti regarding inequality in the distribution of human resources in Tehran province, they found that the highest value of the Gini coefficient (GC) was related to nurses (GC=0.291) in 2007.…”
Section: Discussionmentioning
confidence: 98%
“…25 In their study about the inequality in the distribution of health-care resources in Iran, Lofty et al found that the highest ratio of manpower number per 1000 population was in Ilam province. 29…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that a large number of future practitioners are being trained annually, the Iranian Ministry of Health faces a shortage of human resources due to the lack of funds to hire the required people [55]. The lack of sufficient person-power and higher workloads have caused the discontent of many employees, leading to a reduced quality of services provided to patients [56].…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study [31] on resource distribution between Iran provinces in 2014, mentioning that the dissemination of the health policy segment assets between Iran areas was moderately equivalent. In this manner, health policymakers need to be centered on different parts of availability, for example, circulation of assets as indicated by health needs, distribution of resources within the provinces, and quality of services provision.…”
Section: Health Policies Degradation In Different Areas Of Iranmentioning
confidence: 99%